NUB1 and FAT10 Proteins as Potential Novel Biomarkers in Cancer: A Translational Perspective - Maria Arshad; Mun Chiang Chan; Fuad Ismail; Geok Chin Tan; Francesco Pezzella; Tan Ka Liong; Nazefah Abdul Hamid (MDPI Multidisciplinary Digital Publishing Institute, 2024)
Indexed by WOS/SCOPUS